Intravenous immunoglobulin therapy for dengue capillary leak syndrome in a renal allograft recipient. (19th June 2018) - Subbiah, Arunkumar; Mahajan, Sandeep; Yadav, Raj Kanwar; Agarwal, Sanjay Kumar
Abstract : A 45-year-old man presented 4 months after ABOi renal transplantation with febrile illness and bicytopenia necessitating cessation of mycophenolate mofetil. Dengue non-structural protein 1 antigen (NS1 Ag) test was positive. Lowest total leucocyte count was 3.1×10 9 /L and platelet count was 14×10 9 /L. As fever subsided, patient became tachypneic with abdominal distention and hypotension. Ultrasonographic evaluation revealed ascites, gall bladder wall oedema and bilateral pleural effusion consistent with dengue capillary leak syndrome. He developed massive ascites with abrupt weight gain of 4 kg within 24 hours and worsening renal dysfunction. Patient was deteriorating rapidly in spite of adequate supportive care and we gave a trial of intravenous immunoglobulin (0.5 g/kg/day) for 5 days. Patient improved from day 2, and by day 3, he became haemodynamically stable and recovered completely. Patient was stable at discharge and is on regular follow-up.